A study on the effectiveness factors that influence job performance among employees / Nur Hafizah Ab Hamid and Siti Nabihah Mohamad Jamil - Ab Hamid, Nur Hafizah; Mohamad Jamil, Siti Nabihah (2013)
This topic of research is “The Effectiveness Factors That Influence Job Performance among Employees”. This research tries to determine the relationship between factors of personality, teamwork and commitment, and adaptation on workplace effect to job performances among employees. Researchers want to know the performance of employees by specifically in Johor Bahru. This study to identifies and determines factors that have significant influence on job performance. The respondents for this study are 100 employees in Johor Bharu. The researchers had used convenience sampling as a sampling technique. The process of analyzing and interpreting data has presented by figures and tables using method reliability test, frequency, descriptive statistic, correlations and regression analysis. The researchers also have suggestion and recommendation is to helps the companies to increase their employees job performance.